Reaktualisasi Pendidikan Islam - Sundari, Sundari; Basri, Hasan (LPPM IAIN Sorong, 2025)
Islamic education in the modern era faces increasingly complex challenges. The dynamics of globalization, technological advancements, and shifts in socio-cultural values drive the need for the recontextualization of Islamic education to remain relevant and adaptive. This recontextualization involves not only curriculum refinement but also more contextualized teaching approaches and methods suited to contemporary needs. It entails efforts to integrate Islamic values with general knowledge, aiming to cultivate a generation that is not only knowledgeable but also possesses strong Islamic character. This study seeks to analyze the strategies and approaches that can be applied in the recontextualization of Islamic education and to examine how this process can address current educational challenges. The research method used is a literature review, analyzing various sources, both classical and contemporary, to gain a comprehensive perspective on the recontextualization of Islamic education. The study findings indicate that Islamic education must adapt by developing teacher competencies, innovating learning methods, and adopting an integrative approach, allowing it to meet the demands of the times without compromising its core values